Enhancement of thermal stability and photoluminescent performance of blue light emitting material by incorporating adamantane moieties into carbazole system. Issue 2 (1st February 2018) - Liu, Yingchun; Guo, Jianwei; Yue, Hangbo; Luo, Tao; Tan, Rilin; Li, Xiong
ABSTRACT: A facile route to improve photoluminescent performance and service lifetime of a promising blue light emitting material is reported and demonstrated here using a copolymer system of N -(2-ethylhexyl)-2, 7-carbazole (Cz) and 1, 3, 5, 7-tetrakis- (4-bromophenyl) adamantane (TBA). The copolymers were successfully synthesized by palladium-catalyzed Suzuki coupling reactions. Structure and molecular weight of the materials were characterized by FT-IR and 1 H-NMR spectroscopies, elemental analysis and gel permeation chromatography. The influence of adamantane content on the thermal stability and photoluminescent performance of the synthesized copolymers was investigated in detail. DSC results showed that glass transition temperature increased dramatically, from 68°C for neat carbazole, to 88°C, 120°C and 152°C, after the addition of 10%, 20%, and 30% TBA, respectively. The same trend was found when thermal decomposition temperature at 5% weight loss was evaluated from TGA data. Importantly, this increased stability can be extended to thermo-optical performance, with the Cz-TBA system showing higher color purity and stronger emission intensity within blue light wavelength than carbazole alone. Nevertheless, measurements of emitting spectral stability at a broader temperature range (100–200°C) and photoluminescence quantum yield suggested that there is a delicate trade-off between the performance and adamantane content.